THE RETURN ON INVESTMENT OF DIGITAL LANGUAGE LEARNING TOOLS IN PRIMARY EDUCATION - Sultanova Shohistaxon Shavkatovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
Annotation: This article examines the economic and educational value of investing in digital language learning tools in primary education. It evaluates how technology-based platforms, applications, and interactive resources can improve language acquisition, support differentiated instruction, and enhance overall learning outcomes. The study analyzes both the short-term and long-term returns on investment (ROI), considering factors such as increased student engagement, improved test scores, reduced instructional costs, and the development of 21st-century skills. Case studies from various educational systems are used to demonstrate how effective integration of digital tools can maximize educational impact while ensuring cost efficiency.